2022
DOI: 10.3390/life12030409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diets on Response to Immune Checkpoint Inhibitors (ICIs) Therapy against Tumors

Abstract: Immunotherapy has revolutionized the established therapeutics against tumors. As the major immunotherapy approach, immune checkpoint inhibitors (ICIs) achieved remarkable success in the treatment of malignancies. However, the clinical gains are far from universal and durable, because of the primary and secondary resistance of tumors to the therapy, or side effects induced by ICIs. There is an urgent need to find safe combinatorial strategies that enhance the response of ICIs for tumor treatment. Diets have an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 148 publications
0
12
0
Order By: Relevance
“…A recent study demonstrated that this link is cohort-dependent, and the presence or absence of a single species cannot serve as a predictive biomarker across various populations [ 7 ]. Moreover, several factors, such as diet or concomitant drugs [ 8 , 9 ], were associated with changes in the gut microbiota composition and immune system functions, and their role in ICI efficacy modulation has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that this link is cohort-dependent, and the presence or absence of a single species cannot serve as a predictive biomarker across various populations [ 7 ]. Moreover, several factors, such as diet or concomitant drugs [ 8 , 9 ], were associated with changes in the gut microbiota composition and immune system functions, and their role in ICI efficacy modulation has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to regulating the function of immune cells through the regulation of metabolites such as amino acids, fatty acids and nucleotides in the body, diet can also influence the efficacy of ICIs by affecting the gut microecology. [41,43,63,64] Although our meta-analysis confirmed the PNI was a reliable prognostic indicator, clinicians should use caution when using a single indicator to predict patient prognosis. Because the clinical studies we examined have limitations, like all clinical studies, we suggest that future efforts consider development of an algorithm that considers the PNI along with several additional indicators, such as the neutrophil-to-lymphocyte ratio, red blood cell distribution width, platelet-to-lymphocyte ratio, lung immune prognostic index, and lactate dehydrogenase to more accurately assess patient prognosis.…”
Section: Discussionmentioning
confidence: 66%
“…In addition to regulating the function of immune cells through the regulation of metabolites such as amino acids, fatty acids and nucleotides in the body, diet can also influence the efficacy of ICIs by affecting the gut microecology. [ 41 , 43 , 63 , 64 ]…”
Section: Discussionmentioning
confidence: 99%
“…A KD comprises a high-fat component, very low carbohydrate levels, and low to moderate protein levels, as explained in a recent study. 140 A traditional KD is typically formulated at a 4:1 ratio of fat:carbohydrate plus protein. 141 In this classical formulation, 80–85% of calories are derived from fat, 10–15% from protein, and less than 5% from carbohydrates.…”
Section: Targeted Dietary Interventions and Mechanistic Insights Into...mentioning
confidence: 99%